Synstatin: a selective inhibitor of the syndecan‐1‐coupled IGF1R–αvβ3 integrin complex in tumorigenesis and angiogenesis. (24th February 2013) - Rapraeger, Alan C.
<x xml:space="preserve">Abstract</x> The syndecans are a family of heparan sulfate‐decorated cell‐surface proteoglycans: matrix receptors with roles in cell adhesion and growth factor signaling. Their heparan sulfate chains recognize 'heparin‐binding' motifs that are ubiquitously present in the extracellular matrix, providing the means for syndecans to constitutively bind and cluster to sites of cell–matrix adhesion. Emerging evidence suggests that specialized docking sites in the syndecan extracellular domains may serve to localize other receptors to these sites as well, including integrins and growth factor receptor tyrosine kinases. A prototype of this mechanism is capture of the αvβ3 integrin and insulin‐like growth factor 1 receptor (IGF1R) by syndecan‐1 (Sdc1), forming a ternary receptor complex in which signaling downstream of IGF1R activates the integrin. This Sdc1‐coupled ternary receptor complex is especially prevalent on tumor cells and activated endothelial cells undergoing angiogenesis, reflecting the up‐regulated expression of αvβ3 integrin in such cells. As such, much effort has focused on developing therapeutic agents that target this integrin in various cancers. Along these lines, the site in the Sdc1 ectodomain that is responsible for capture and activation of the αvβ3 or αvβ5 integrins by IGF1R can be mimicked by a short peptide called 'synstatin', which competitively displaces the integrin and IGF1R kinase from the syndecan and inactivates the complex. This review summarizes our current knowledge of the Sdc1‐coupled ternary receptor complex and the efficacy of synstatin as an emerging therapeutic agent to target this signaling mechanism.